Libraries and their architecture in the 21st century - Miersch-Süß, Ines; Miersch-Süß, Ines (De Gruyter Saur, 2021)
Libraries have quietly changed over the last 20 years. They have adapted early and consciously to the changes of digitalization, they have recognized the changed need of their users for collaborative work and derived new spatial concepts from this. Transparency and access to information, knowledge and encounters are the prerequisites for holistic social development. It is the challenge of the 21st century as the information age. This book presents the latest developments in library architecture as well as the way scientists and architects are meeting this challenge. With essays by Achim Bonte, Catherine Lau, Max Dudler, Georg Gewers, Henning Larsen Architects, MSAO Architects, Claudia Lux, Marco Muscogiuri, Schmidt Hammer Lassen Architects, Snøhetta, Sauerbruch Hutton, gmp Architects followed by a conversion with Oliver Jahn and Dante Bonuccelli. Watch the first Knowledge Talk: KNOWLEDGE FOR ALL with Prof. Dr. Claudia Lux and Prof. Dr. Eike Schmidt on YouTube: https://www.youtube.com/watch?v=aKk_wRBGt1E The new role of the Uffizi, Florence and the opening of knowledge to a wider society are subject of the first Knowledge Talk with Prof. Dr. Claudia Lux and Prof. Dr. Eike Schmidt live from the Uffizi on International Museum Day, May 18, 2021. The Knowledge Talk connects the topics from the new publication "Libraries and Their Architecture in the 21st Century". Der zweite Knowledge Talk fand am 5. Juli 2021 in der Zentralbibliothek Zürich statt: Max Dudler im Gespräch über seine Bibliotheken. Lassen Sie sich diesen informativen Austausch nicht entgehen:https://www.zb.uzh.ch/de/events/max-dudler-im-gesprach-uber-seine-bibliotheken?date=316